Study on Morphological and Microscopic Characteristics of Abelmoschus sagittifolius (Kurz) Merr. in Vietnam - Huyen, Pham Thanh; Nga, Nguyen Quynh; Ngoc, Pham Thi; Viet Hung, Lai; Truong, Phan Van; Van Hieu, Nguyen; Tu, Dang Minh; Thi Ha Ly, Nguyen; Thao, Duong Thi Phuong; Nhung, Pham Thi Hong; Long, Dinh Doan (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
Sam bo chinh ( Abelmoschus sagittifolius (Kurz) Merr.) is a precious medicinal plant that has been exploited and planted in Vietnam for a long time. However, the morphological characteristics of this plant is easy to confuse with other species of the same genus. In addition, the microscopic characteristics and medicinal powder composition of this medicinal plant have not been comprehensively described. The present investigation was aimed to determine the morphological and microscopic characters of Sam bo chinh using comparative morphology, anatomical research and medicinal powder analysis. The complete description of morphological and microscopic characteristics reported in this study will serve as valuable data for the conservation and development of this species in Vietnam. Keywords Morphology, microscopic characteristics, medicinal plant, Abelmoschus sagittifolius. References [1] The International Plant Names Index and World Checklist of Selected Plant Families 2021, http://powo.science.kew.org/taxon/urn:lsid:ipni.org:names:558042-1, (accessed on: 7th May 2021). [2] P. H. Ho, Medicinal Plants in Vietnam, Tre Publishing House, Ho Chi Minh, 2006, pp. 112 (in Vietnamese). [3] D. H. Bich et al., Medicinal Plants and Medicinal Animals in Vietnam, Science and Technics Publishing House, Hanoi, 2006, pp. 690-693 (in Vietnamese). [4] Ministry of Health, Vietnamese Pharmacopoeia V, Medical Publishing House, Hanoi, 2018, pp. 1310-1311 (in Vietnamese). [5] G. L. D. Chen, Y. Y. Liu, G. X. Ma, W. Zheng, X. B. Sun, X. D. Xu, A New Cadinane Sesquiterpenoid Glucoside with Cytotoxicity from Abelmoschus sagittifolius, Natural Product Research, Vol. 33, 2019, pp. 1699-1704, https://doi.org/10.1080/14786419.2018.1431635. [6] D. T. Vui, Study Chemical Composition and Pharmacological Effects towards The Treatment Gastric Ulcers of The Roots of Abelmoschus sagittifolius (Kurz) Merr. Malvaceae, Doctoral Thesis, National Institute of Medicinal Materials, Hanoi, 2007 (in Vietnamese). [7] D. T. Xuyen, Some New Information on The Genus Abelmoschus Medic. in Vietnam, Scientific Report on Ecology and Biological Resources, The First National Conference, Institute of Ecology and Biological Resources, Hanoi, 2005 (in Vietnamese). [8] N. N. Thin, Methods of Plant Research, Vietnam National University Press, Hanoi, 2007 (in Vietnamese). [9] N. Ba, Plant Morphology, Vietnam Education Publishing House, Hanoi, 2006 (in Vietnamese). [10] N. V. Than, Testing Medicinal Herbs by Microscopic Method, Science and Technics Publishing House, Hanoi, 2003 (in Vietnamese). [11] P. H. Raven, H. D. W. Zhengyi, Flora of China, Science Press (Beijing) & Missouri Botanical Garden (St. Louis), China and USA, 2007, pp. 283-285. [12] Abelmoschus moschatus (L.) Medik, http://uphcm.edu.vn/caythuoc/index.php?q=book/export/html/298, (accessed on: May 25th, 2020) (in Vietnamese)